Pengaruh Pelatihan Karyawan dan Kompensasi Terhadap Kinerja Karyawan - Muhammad Andre Fauzi Akbar; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
This study aims to analyze the effect of employee training and compensation variables on employee performance variables. The type of research used is quantitative method with descriptive analysis. The data collection technique was carried out online in the form of a questionnaire with the help of the Microsoft Forms application using a Likert scale of one to five and obtained by a simple random sampling method on 32 respondents with the criteria of office workers or employees. The data analysis techniques used in this study are: Outer Model with the calculation of Convergent Reliability, Discriminant Validity, Composite Reliability, Cronbach's Alpha, VIF and Inner Model with calculations on R-Square, Adjusted R-Square, and f-Square hypothesis testing on the calculation of T statistic, P-Value, and Original Sample using SmartPLS (Partial Least Square) software version 4. The results showed that: 1) Employee training has a positive and significant effect on employee performance with t test results of 3,774, p-value 0.000, and positive Original Sample. 2) Compensation has a positive and significant effect on employee performance with a t-test result of 3.454, p-value 0.001, and positive Original Sample. 3) Employee training and compensation together have a positive and significant effect on employee performance with an R-Square result of 0.650 or 65% influence. Recommendations from this study are to add independent variables and expand the population area for better results.